Erbium-doped fiber amplifiers principles and applications - Desurvire, Emmanuel (John Wiley & Sons, 1994)
Written by one of the pioneers in the field, this unique reference provides researchers, engineers, and system designers with detailed, interdisciplinary coverage of the theoretical underpinnings, main characteristics, and primary applications of EDFAs.